Prognostic impact of pretransplant iron overload measured with magnetic resonance imaging on severe infections in allogeneic stem cell transplantation. (31st May 2013) - Virtanen, Johanna M.; Itälä‐Remes, Maija A.; Remes, Kari J.; Vahlberg, Tero; Saunavaara, Jani P.; Sinisalo, Marjatta; Parkkola, Riitta K.
Abstract Objective Infections and graft‐versus‐host disease (GVHD) are the main causes of transplant‐related mortality (TRM) of patients undergoing allo‐SCT. The role of iron overload (IO) has been debated in this context. Studies, performed with non‐specific surrogate markers of iron, suggest that IO predicts poor outcome after allo‐SCT. Methods In this prospective study, we quantified pretransplant IO with MRI‐based hepatic iron concentration (HIC) measurement; the degree of IO was used to predict infections, GVHD, and mortality after allo‐SCT. Logistic univariate, multivariate, and Cox's regression analyses were performed. Results Iron overload was present in 78% of the patients (HIC>36 μmol/g). The median HIC was 98 μmol/g (range 5–348). There were no cases of cardiac iron excess. IO was significantly associated with severe infections during the early post‐transplant period (for every 10 μmol/g increase OR: 1.15, 95% CI 1.05–1.26, P = 0.003). The odds for severe infections increased 6.5‐ (>125 μmol/g OR: 6.5, P = 0.013) to 14‐fold (>269 μmol/g OR: 14.1, P = 0.040) with increasing HIC. IO was found to be associated with reduced risk of acute and chronic GVHD. Although TRM was due to infection‐related deaths, IO was not associated with TRM or OS. Conclusion Pretransplant IO, measured with a direct MRI‐based measurement, predicts severe infections in the early post‐transplant period.